Identification of Local Culinary Potential in Supporting The Development of Kerujuk Ecotourism Village, North Lombok Regency - Abdullah, Nabila Nurrahmadina; Dienaputra, Reiza D; Yustikasari; Fajriasanti, Ruwaida; Rizkiyah, Nurul Farikhatir (Journal of Mandalika Review, 2026)
Introduction:  Local culinary traditions are increasingly recognized as valuable assets in promoting sustainable tourism, particularly in rural and ecotourism destinations. This study explores the potential of traditional food as a tourism attraction in Kerujuk Ecotourism Village, North Lombok, Indonesia. Grounded in the village's rich cultural heritage and natural resources, local cuisine offers opportunities for community-based economic development, cultural preservation, and environmental sustainability. However, the realization of this potential is constrained by challenges such as limited promotion, inadequate infrastructure, and weak coordination among stakeholders. Drawing on literature and comparative case studies, this research identifies key supporting and inhibiting factors in the development of culinary tourism. The findings aim to provide strategic insights for integrating local food systems into sustainable tourism planning, highlighting their role in enhancing visitor experience, regional identity, and inclusive economic growth. Methodology: This study used a qualitative descriptive method with a case study approach to explore the local culinary potential of Kerujuk Ecotourism Village. Data were collected through observation, interviews, and documentation, then analyzed using an interactive model involving data reduction, display, and conclusion drawing. Triangulation was applied to ensure data validity. Findings: This study found that Kerujuk Ecotourism Village has diverse local culinary products with strong cultural value, supported by natural resources and community participation. However, challenges remain in scarcity of ingredients, hygiene, business management, and marketing. Conclusion: Local cuisine in Kerujuk has strong potential to support tourism development. Strategic improvements in training, sanitation, and promotion are essential to enhance its competitiveness and sustainability.